Ավագ դպրոցականների ինքնագիտակցության առանձնահատկությունները (ՀՀ կրթական հաստատությունների օրինակով) - Է. Ս. Մաթևոսյան (ՀՀ ԳԱԱ հրատ.)
Существует много факторов, меняющих самосознание старшеклассников: школьная атмосфера, окружение, гендерная принадлежность и т. д. There are many factors that change the self-consciousness of senior pupils: the school environment, gender identity, etc. In addition, typical for this age group physiological processes have a serious impact on the formation of self- consciousness, too.
Keywords: L Education; LB Theory and practice of education